Penguatan Motivasi Belajar Melalui Self-Regulated Learning Mahasiswa pada Pembelajaran Daring Dimasa Pandemi Covid-19 - Abdul Kadir; Akif Khilmiyah (Universitas Muhammadiyah Kuningan, 2023)
This study aims to analyze the causes of low learning motivation and find the keys to increase learning motivation. This type of research uses a qualitative approach with phenomenological methods. Informants were selected using the snowball sampling technique. Informants in this study focused on Yogyakarta students who experienced a reduction in motivation and were selected based on the required characteristics. Data collection techniques use interviews, observation and documentation, and data analysis through reduction analysis. The data validity used source triangulation. This study resulted in (1) the causalities of low learning motivation: they felt bored with the online learning process, had less effective zoom learning, had difficulty completing assignments due to internet connection, lack of interaction with lecturers, and less supervision during the learning process, and lecturers giving more theory than practice (Field). (2) Solutions to improve learning: Parent's advice, do assignments according to things you like, set learning targets, grow motivation to get good grades, and diligently participate in studies. Have courses that match your interests